Acute rehabilitation after resuscitative endovascular balloon occlusion of the aorta (REBOA) in major trauma - Rich, Jessica Anne (BMJ Case Rep, 2017)
We report a 23-year-old woman admitted post cyclist versus heavy goods vehicle accident in December 2014. This was the second case the life-saving procedure, that is, resuscitative endovascular balloon occlusion of the aorta (REBOA) was performed on at the roadside. This advanced procedure was performed due to the extensive haemorrhage from this patient’s complex pelvic fracture. As a result of REBOA, the patient consequently lost her left lower limb and underwent a variety of complex pelvic and lower limb surgeries. The patient was admitted to the acute critical care unit and underwent repeated operations and was not ready to start active rehabilitation until 12 days into her admission. Prior to this she was on movement restrictions and received physiotherapy for limb care and dietetics in order to meet her nutritional requirements. The patient was stepped down to a ward setting and started on an extensive physiotherapy programme and was then transferred to the rehabilitation unit for amputees at Roehampton.